Estimation of crop water requirement and irrigation scheduling of KCEAT instructional farm using cropwat model - MEGHA P; Sabeena Shahul; Dr. Rema K. P (Guide) (Tavanur 2013 Department of Irrigation & Drainage Engineering)
Estimation of crop water requirement and irrigation scheduling of KCEAT instructional farm using cropwat model
Estimation of crop water requirement and irrigation scheduling of KCEAT instructional farm using cropwat model